"Conocimientos sobre gestión sanitaria de los aspirantes al Gobierno Municipal en una provincia norteña" - Baca Ynostroza, María Antonieta (2008)
This research study is of descriptive and qualitative type, with the objective of verifying the knowledge on health municipal management, a guide interview was applied, which was designed by the author of this work, to 15 applicants to the municipal government of the different political groups that participated in the electoral process in 2006. The obtained conclusions were the following: In general, the applicants to the municipal government have knowledge about the health municipal management, but the emphasis of their knowledge is due to the influence of the image that gives the health – illness healing and is focused on the healing of the illness and not in promoting healthy environments and determiners. The decentralization concept is understood in the sense of “deconcentration” and assistance without taking account the report in the coordination with the entities of the health sector to prevent problems an unnecessary expenses in sanitary actions. The divergences are links like political platforms of the political movements that participate in the electoral contests. Most of their plans are convergent. However, knowing each interviewed person is diverse. All the political groups present speakers who know those who do not know the health municipal management.